The Advantages Of Using Information Technologies In Teaching English As A Foreign Language - Vasiyeva Shakhnoza Islamovna (Genius Publishing Group, 2024)
The use of information technology (IT) in English language teaching has revolutionized the learning experience, offering numerous advantages for both teachers and students. This article explores the positive aspects of integrating IT into English language learning. Nowadays the importance of incorporating Information Technologies in Foreign Language (FL) education has often been emphasized, especially by foreign language pedagogy scholars. The aim of the paper was to summarize the results of the observations carried out at institutes in order to map ways of improving students’ foreign language were developed suitably and sufficiently in the observed EFL lessons. The analysis showed that EFL courses at the institution tend to regard the importance of integrating skills with the usage of ICT in FL education. As a result of discussion and analysis we concluded that it is pivotal to make use of 21st century skills in the process of teaching EFL.
Keywords: English as a foreign language; Information Technologies; Integrated skills; teaching